Influence of Organizational Communication on Employee Satisfaction at PT. Perkebunan Nusantara III Sei Putih - Indah Mawarni (Junal Ilmu Manajemen, 2018)
This study aims to Determine the effect of organizational communication on employee job satisfaction at PT. Perkebunan Nusantara III Sei Putih. The research method used in this study is a quantitative method. Quantitative Methods is a research method that aims to describe what happens to the object with an effort to describe, record, analyze and interpret existing data.The population in this study were all employees of PT. Perkebunan Nusantara III Sei White, amounting to 50 people, while the sample is the entire population. Sampling uses a saturated / roomates census sampling technique uses the entire group of research of data in the population as research elements and subjects. The statistical test used is using the classic assumption test, hypothesis testing, simple linear analysis, correlation coefficient and determinant coefficient.The results of this study indicate that partially a significant influence on organizational communication on employee job satisfaction at PT. Perkebunan Nusantara III Sei Putih for tcount 2.978> 1.667 table. Then H0 is rejected Ha is accepted and a significant value of 0.006 t is smaller than 0:05, so the hypothesis is accepted that organizational communication (X) has a significant effect on job satisfaction (Y) at PT. Perkebunan Nusantara III Sei Putih.